(x+9)(x+12)=0

Simple and best practice solution for (x+9)(x+12)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+9)(x+12)=0 equation:


Simplifying
(x + 9)(x + 12) = 0

Reorder the terms:
(9 + x)(x + 12) = 0

Reorder the terms:
(9 + x)(12 + x) = 0

Multiply (9 + x) * (12 + x)
(9(12 + x) + x(12 + x)) = 0
((12 * 9 + x * 9) + x(12 + x)) = 0
((108 + 9x) + x(12 + x)) = 0
(108 + 9x + (12 * x + x * x)) = 0
(108 + 9x + (12x + x2)) = 0

Combine like terms: 9x + 12x = 21x
(108 + 21x + x2) = 0

Solving
108 + 21x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(12 + x)(9 + x) = 0

Subproblem 1

Set the factor '(12 + x)' equal to zero and attempt to solve: Simplifying 12 + x = 0 Solving 12 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + x = 0 + -12 x = 0 + -12 Combine like terms: 0 + -12 = -12 x = -12 Simplifying x = -12

Subproblem 2

Set the factor '(9 + x)' equal to zero and attempt to solve: Simplifying 9 + x = 0 Solving 9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + x = 0 + -9 x = 0 + -9 Combine like terms: 0 + -9 = -9 x = -9 Simplifying x = -9

Solution

x = {-12, -9}

See similar equations:

| 7m+2n-2m+11n= | | x-80=40 | | 5.7m-3=2.7m+6 | | 1.45x+7(0.15x-2.8)=14.4 | | 5x-2=-18-3x | | 13-2x-5x+9= | | 2.5x-(40+1.75x)=550 | | 0.7=0.4+x-0.35 | | 20x+12=0 | | 16+2(x+4)(x-4)-x=-x+16 | | 6(y-1)-2y=2(2y-3) | | 0.7=0.4+P(B)-0.35 | | .25x-.75y=-1 | | 7.4x-4-5.2x=2.6 | | 4(5x+4)=3x+36+7x | | x^2+3y=-1 | | 8(m+6)+4=36+5m | | -3.6x+1.3=-16.7 | | 21x+6=23x-2 | | G(x)=x^2-x-5 | | -2.1-1.5=x+1.3 | | 3=t+5-3t | | 4x-5=6x+3 | | 2(x+5)=2x-5 | | 6=v+0.84 | | -50-0.25=-75 | | 110x=90(2-x) | | 1.29+3.9-9.99+6.1= | | X-3(x-5)=2x-11 | | 5y-x=-1 | | W^3+w^2-2w=8 | | 6a-3ab-4ak+2bk= |

Equations solver categories